DNA-based Nanostructures as Novelty in Biomedicine - Mohammadi, Ameneh; Gill, Pooria; Ebrahimnejad, Pedram; Abediankenari, Said; Kashi, Zahra (Novelty in Biomedicine, 2022)
The application of nanocarriers in medicine and pharmaceuticals suggests a new procedure in nanotechnology terminology, nanomedicine. DNA has been significantly highlighted due to its amazing functionality and nature as a nanomaterial in biomedicine. Given that DNA is biocompatible, its use as a nanomaterial in medicine provides an excellent prospect for the rational engineering of DNA nanostructures. According to new approaches in disease treatment at gene levels, gene therapy, DNA as a nanomedicine plays an essential role in the medical sciences. In this field, researchers have published enormous documents regarding the applications of DNA and DNA-based nanostructures as drug or gene nanocarriers, DNA-based diagnostics, and DNA nano vaccines. In this review, the novelty of DNA-based nanomedicine has been considered.